ECONOMIC RELATIONS BETWEEN UZBEKISTAN AND AZERBAIJAN: RETROSPECTIVE AND PRESENT - Farkhod Adilov (Social science and innovation, 2023)
This article, based on sources, analyzes information about the history, modernity and prospects for economic relations between the republics of Uzbekistan and Azerbaijan. In particular, information is provided on the historical roots of economic relations between countries and the main aspects of relations in the Soviet era, and modern relations are analyzed on the basis of economic indicators and conclusions and suggestions are made